2021
DOI: 10.3390/jcm10132963
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Conventional and Stereotactic Microwave Ablation for Intrahepatic Cholangiocarcinoma

Abstract: Background: The incidence and mortality of intrahepatic cholangiocarcinoma (ICCA) is increasing worldwide and curative treatment options are limited due to the aggressive tumor biology and often late diagnosis. Resection of the primary tumor remains the only curative therapy available, as the benefit of palliative chemotherapy and radiotherapy is relatively small. In contrast to hepatocellular carcinoma, minimal-invasive thermal tumor ablation, and in particular stereotactic tumor ablation for small primary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Ratti et al showed that laparoscopic LND could result in a similar number of LN to open surgery with lower complications incidence related to LND. According to the guidelines, LND was acknowledged as a standard treatment for ICCA; those conflicting published results suggested that LLR for ICCA currently may not be totally optimal [ 16 , 19 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ratti et al showed that laparoscopic LND could result in a similar number of LN to open surgery with lower complications incidence related to LND. According to the guidelines, LND was acknowledged as a standard treatment for ICCA; those conflicting published results suggested that LLR for ICCA currently may not be totally optimal [ 16 , 19 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…MWA can be also combined with other locoregional therapies such as trans-arterial conventional chemoembolization, as was shown in a retrospective study which reported survival at 6, 12 and 24 months of 88.5%, 69.2% and 61.5%, respectively [48]. Furthermore, stereotactic navigation systems contribute to shortening the duration of ablation sessions by increasing the accuracy of access, even in challenging anatomic locations of the liver or for tumors located in proximity to important vasculature as well as for tumors invisible on ultrasound and CT [74,75]. Thermal ablative therapies (RFA and MWA) display promising potential as treatment modalities for iCCA with satisfactory outcome and good safety profile as was shown in published meta-analyses and systematic reviews [35,66,73] showing pooled technical efficacy of 91.9%, major complications incidence of 5.7% and pooled OS at 1, 3 and 5 years of 82.4%, 42.1% and 28.5%, respectively, with primary tumors showing higher 3-year OS rates than recurrent ones [66].…”
Section: Microwave Ablationmentioning
confidence: 99%
“…Studies examined in this review used MWA for primary unresectable ICC, recurrent ICC after SR, and in the case of larger tumors, with palliative intent ( Table 2 ). Many studies included only patients with a largest tumor size of <5 cm and <3 lesions, though some studies included patients with larger tumors, up to 10 cm [ 25 , 26 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Most eligible patients were required to have sufficient coagulation parameters, platelet count, liver and kidney function, and adequate performance status [ 25 , 33 , 34 , 36 , 39 , 40 , 42 , 43 , 44 ].…”
Section: Locoregional Treatment For Intrahepatic Cholangiocarcinomamentioning
confidence: 99%
“…Like RFA, studies have shown that MWA is well-tolerated in the treatment of ICC. Major complications ranged from 0–20% in examined studies and consisted of liver abscess, pleural effusion, ascites, hepatic failure, and tumor seeding [ 25 , 26 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Minor complications were common and included post-ablation syndrome, thrombocytopenia, a transient elevation in liver function tests (LFTs), and portal vein thrombosis [ 25 , 39 , 42 , 44 ].…”
Section: Locoregional Treatment For Intrahepatic Cholangiocarcinomamentioning
confidence: 99%
See 1 more Smart Citation